Lessons learnt from a series of hemodynamic and interventional complications during pulmonary valvotomy and device closure of ventricular septal defect - Anil Kumar Singhi; Sivakumar Kothandam (Wolters Kluwer Medknow Publications, 2015)
In an adolescent girl with coexistent valvar pulmonary stenosis (PS) and muscular ventricular septal defect (VSD) causing right to left shunt and severe cyanosis, a series of complications were encountered during transcatheter intervention. After balloon pulmonary valvotomy (BPV) and device closure of the VSD, dynamic infundibular hypercontractility elevated the right ventricular (RV) systolic pressures leading to embolization of the device into the left ventricle. During retrieval of the device from the left ventricular outflow tract (LVOT), there was injury to the atrioventricular nodal tissue resulting in transient complete heart block. Even though the device was successfully retrieved out from the right femoral arterial access, there was a retroperitoneal hematoma causing severe anemia. A combination of dynamic infundibular obstruction, intravascular volume depletion caused by hemorrhage, low oxygen carrying capacity due to anemia, and inotropes resulted in a life-threatening hypercyanotic spell. Once this combination of suicidal hypercontractile right ventricle, anemia, and dehydration was recognized; management of the pathophysiology resulted in recovery of the patient. On a subsequent day, device closure of the VSD was complicated by unstable device position, but was finally achieved by an innovative device stabilization technique. We propose to explain the basis of hemodynamic and procedural complications, their recognition, and management. During preparatory stage before interventions in patients with multiple defects, which are linked by strong hemodynamic interdependence, meticulous planning should be done and multiple untoward events should be foreseen. While a few complications were completely unanticipated, some others could have been predicted.